The freeing of Nelson Mandela - Beecroft,Simon (Tunbridge Wells, Kent : Ticktock, 2003)
A biography of the Black South African leader who became a civil rights activist, political prisoner, and president of South Africa, told in the context of the history of his country.
Includes bibliographical references and index.
Keywords: Mandela, Nelson, 1918 -- Juvenile literature; Political prisoners; Presidents -- South Africa